2021
DOI: 10.1242/jcs.257790
|View full text |Cite
|
Sign up to set email alerts
|

EVI/WLS function is regulated by ubiquitylation and is linked to ER-associated degradation by ERLIN2

Abstract: WNT signalling is important for development in all metazoan animals and is associated with various human diseases. The Ubiquitin-Proteasome System (UPS) and regulatory ER-associated degradation (ERAD) have been implicated in the production of WNT proteins. Here, we investigated how the WNT secretory factor EVI/WLS is ubiquitinated, recognised by ERAD components and subsequently removed from the secretory pathway. We performed a focused, immunoblot-based RNAi screen for factors that influence EVI/WLS protein st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 73 publications
1
22
1
Order By: Relevance
“…First, Jean‐Paul Vincent (The Francis Crick Institute, UK) discussed mechanisms underlying Wnt gradient formation (McGough et al, 2020). Then, Michael Boutros (German Cancer Research Center, Germany) talked about ERAD‐mediated regulation of Evi/Wls protein, which is specifically involved in secretion of Wnt proteins (Wolf et al, 2021). David M. Virshup (Duke‐NUS Medical School, Singapore) described telocyte‐mediated delivery of Wnt ligands in the intestinal stem cell niche, and Steffen Scholpp (University of Exeter, UK) presented cytoneme‐mediated transport of active Wnt5b/Ror2 complexes in zebrafish (Brunt et al, 2021).…”
Section: Oral Presentationsmentioning
confidence: 99%
“…First, Jean‐Paul Vincent (The Francis Crick Institute, UK) discussed mechanisms underlying Wnt gradient formation (McGough et al, 2020). Then, Michael Boutros (German Cancer Research Center, Germany) talked about ERAD‐mediated regulation of Evi/Wls protein, which is specifically involved in secretion of Wnt proteins (Wolf et al, 2021). David M. Virshup (Duke‐NUS Medical School, Singapore) described telocyte‐mediated delivery of Wnt ligands in the intestinal stem cell niche, and Steffen Scholpp (University of Exeter, UK) presented cytoneme‐mediated transport of active Wnt5b/Ror2 complexes in zebrafish (Brunt et al, 2021).…”
Section: Oral Presentationsmentioning
confidence: 99%
“…Interestingly, the level of Evi/Wls is regulated by the ERAD pathway, and the post-translational modification of Wnt controls Evi/Wls stability [128]. In a subsequent study, an RNAi-based screen was use to establish that Evi/Wls quantity control is orchestrated by a consortium of ERAD-associated factors [129].…”
Section: β-Cateninmentioning
confidence: 99%
“…The cargoreceptor Evi/Wls is recycled from the plasma to the ER by a retromer-dependent mechanism to be loaded again with WNTs [ 19 , 20 ]. Recently, it has been shown that the abundance of WLS/Evi in the ER is regulated by its ubiquitination and subsequent degradation, thereby restricting the secretion of WNTs (Wolf and Boutros, Development, in press) [ 21 ].…”
Section: Introductionmentioning
confidence: 99%